(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
This article attempts to identify elements of dualism through objects and image pairs found in Malay proverbs. Based on the collected data, there are 31 proverbs from 4359 Malay proverbs that contain elements of dualism. For instance, the combination of "padi-lalang" (lit. "rice plant-weeds"), "cempedak-nangka" (lit. "cempedak- jackfruit") and "asam-garam" (lit. "sour-salty") were taken from UKM’s www. malaycivilization.com database. Each example of these combinations was analysed. In analysing the data, the inquistive semantics approach and the Cross-Reference Framework (Rangka Rujuk Silang) was employed. A combination of the data with theory, philosophy and culture finally yielded the true meanings of the Malay proverbs and ultimately reflect the Malay mind. The study found that the "paddy-weeds" and "cempedak-jackfruit" pairs indicate contradiction. On the other hand, the "sour-salty" pairing does not indicate contradiction but complementation. The inquisitive semantics approach is capable of revealing various aspects of wisdom and philosophy contained in Malay proverbs. Keywords: dualism, Malay proverbs, Malay mind, inquisitive semantics, bridging cross references